The Interplay Between Cultural Heritage and Syntactic Evolution : A Cross-Generational Analysis of Language Shift in Multilingual Societies - Kamsinah Kamsinah; Nurasia Natsir; Aisyah Aulia Putri (International Journal of Educational Research, 2025)
This study examines the relationship between cultural heritage and syntactic evolution in multilingual societies, focusing on cross-generational language transmission. Employing a mixed-methods approach, it analyzes linguistic practices, cultural narratives, and syntactic patterns across three generational cohorts in five distinct multilingual communities. Findings reveal significant generational shifts, with elders preserving traditional syntax linked to cultural rituals, while younger cohorts exhibit syntactic simplifications and hybrid constructions influenced by dominant languages. Statistical analyses underscore the role of cultural practices in shaping linguistic patterns, highlighting the dynamic interplay between heritage preservation and linguistic innovation in contexts of societal bilingualism and intercultural interaction. The research demonstrates that syntactic changes correlate strongly with the frequency and depth of cultural engagement, with participants who actively participate in traditional practices showing greater retention of heritage language syntactic features. Furthermore, we identify specific linguistic mechanisms through which cultural transmission influences syntactic maintenance and innovation, including ritualized speech patterns, narrative structures, and metaphorical expressions embedded in cultural practices. This study contributes to theoretical understandings of language change by proposing a cultural-syntactic framework that helps explain the variable trajectories of heritage languages in diverse multilingual contexts.